Recurrence of parasite in epigastric heteropagus - Takeshi Shirai; Yoshinori Hamada; Tatsuma Sakaguchi; Hiroshi Hamada; Kengo Hattori; Yusuke Nakamura; Masanori Kon (Elsevier, 2017)
Epigastric heteropagus (EH) refers to asymmetrically conjoined twins in whom an incomplete parasite is attached to the autosite's epigastric region from the xiphisternum to the umbilicus. We herein report an extremely rare case of EH in which unexpected rapid recurrence occurred 22 months after excision of the parasite. The recurrent mass comprised the intestinal wall with peristalsis-like movement, urogenital tissues, and hepatic tissue of the parasite. The recurrence was caused by a remnant of the parasite that extended from the autosite's xiphisternum to intra-abdominal cavity.